Experience-based know-how, learning and innovation in German SMEs: An explorative analysis of the role of know-how in different modes of innovation - Harm Alhusen (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2020)
The 'doing-using-interacting mode' of innovation (DUI) is considered an important component of innovative activity. It describes informal innovative activities and complements the 'science-technology-innovation mode' (STI) which is based on research and development. A common demarcation criterion between both modes of innovation is the relevance of experiencebased knowledge, know-how and know-who for the DUI mode of innovation whereas the STI mode of innovation is said to rely on codified knowledge, know-what and know-why. Based upon 81 in-depth interviews with German SMEs and regional innovation consultants, this work focuses on the role of experience-based know-how for SMEs innovations within different modes of innovation. Experience-based know-how is found to be important for all modes of innovation, regardless of an SMEs mode of innovation. Results from qualitative interviews show that firms view experience-based know-how as important for at least one of the following domains: product innovation, business process innovation & organizational routines and customer knowledge. However, the acquisition, transfer and transformation of experience-based know-how can strongly differ, depending on the respective mode of innovation. As a recommendation, the idea that know-how is a suitable demarcation criterion for modes of innovation should be revised in future research.
Keywords: O3; O30; O31; R10; 330; DUI; STI; tacit knowledge; experience-based knowledge; learning processes; modes of innovation